Benetton subverte padrões publicitários - Coelho, Marcelo (Comunicação & Educação, 1995)
The presence of advertising photographer Oliviero Toscani in São Paulo and his exhibition of photos for Benetton are the pretext for a critical evaluation of the mode of advertising carried out by the company.